PENERAPAN SISTEM MAKE TO ORDER SEBAGAI STRATEGI PENGEMBANGAN WIRAUSAHA KREATIF PADA GENERASI Z DI WIRAUSAHA MERDEKA 3 UNTAG SURABAYA - Putri Nur Aini; Awin Mulyati (Triwikrama: Jurnal Ilmu Sosial, 2024)
This research aims to describe the application of the make to order system as a strategy for developing creative entrepreneurship in generation z. The approach used in this research is a qualitative approach with a case study method, the data sources used are the first source from interviews and the second source from the literature. The data collection techniques used were interviews and observations, while the data analysis techniques used were thematic techniques. The results of this research are that there are two sub-discussions, namely the Implementation of the Make to Order (MTO) System in Creative Entrepreneurship and the Relevance of the MTO Strategy to the Characteristics of Generation Z, which in this case is explained in detail in the discussion section.